Better Board Education for Better Leadership and Management in the Health Sectors of Low and Middle Income Countries - Sikipa, Godfrey; Osifo-Dawodu, Egbe; Kokwaro, Gilbert; Rice, James A. (Frontiers in Public Health, 2019)
Board member education must be elevated within the curricula of leadership development programming in Low and Middle Income Countries (LMICs) across the globe. When properly trained and supported, the community, business, and health sector leaders serving on these boards can create the conditions within which those who deliver and manage health services are more likely to successfully achieve the mission of their organizations. The importance of incorporating education for governing body members into health sector leadership development programming, and three strategies for board development, are defined in in this article.